Acquired Umbilico-Inguinal Fistula with Persistent Discharge due to Suture Reaction: A Case Report and Review of the Literature - Muazez Cevik (Case Reports in Medicine)
The aim of this paper is to stay a very rare umbilico-inguinal fistula (UIF) resulting from a delayed suture reaction after the use of silk suture to repair an inguinal hernia. A 3-year-old boy presented with persistent umbilical discharge. The initial diagnosis was omphalitis and he was treated with broad-spectrum antibiotics but a UIF was subsequently diagnosed. Surgery was performed to ascertain the cause of the UIF. This case demonstrates that silk suture used in inguinal hernia repair can lead to a UIF, which should be considered in the differential diagnosis of a patient presenting with persistent umbilical discharge.